Application of Mathematical Packages in Education Using the Example of the Mathematical Package Maple (Pedagogical Cluster-Journal of Pedagogical Developments, 2023)
the article discusses the relevance of using mathematical packages in the educational process. Universal mathematical packages provide new and extensive opportunities for improving education at all stages, without exception. Problems associated with the use of mathematical packages and ways to solve these problems are also noted. As an example, we consider solving non-standard equations graphically using the Maple program